Meningkatkan Pola Mengajar Guru Melalui Implementasi Manajemen Perencanaan Berbasis Data (PBD) dalam Kurikulum Merdeka - Sri Mundaryati (Yayasan Indonesia Bermutu, 2022)
The purpose of writing is to improve teacher teaching patterns based on the root problems faced by schools based on the results of educational report cards related to the quality of learning related to classroom management and reflection on teaching practices that are still not good. The essence of this management is how a principal empowers all aspects of the school, to be managed professionally and totally, through the stages described through the cycle model. In addition, how the components in the cycle can be synergized so that the teaching pattern of teachers can improve and change from the old paradigm of teaching to a new paradigm with an independent curriculum and a project to strengthen the profile of Pancasila students. With data-based planning (PBD) with the pattern of Correcting Reflection Identification (IRB) steps, it turns out to be able to improve teacher teaching patterns from each cycle. The following is evidence of changes in each cycle, the teacher's ability related to the learning climate in the classroom from 37.5% increased to 87.5%. Ability in learning management strategies from 12.5% increased to 62.5%. Abilities related to giving feedback increased from 50% to 87.5 and abilities related to self-improvement from 12.5 to 87.5. The key to improving learning patterns in the classroom is to know the root of the problem, be able to reflect and agree to improve themselves.